Study of irrigation performance index in Saba irrigation area - Putu Indah Dianti Putri; Putu Ardi Suputra; I Ketut Nuraga (Journal of Infrastructure Planning and Engineering, 2022)
Saba Irrigation Area is located in Gerokgak and Seririt District, Buleleng regency, Bali. The assessment of the irrigation performance index is required to maintain the value of irrigation asset function and condition. Some problems occur in the irrigation area from the standard area of 1548 ha, but the productive land is around 889 ha or about 57% of the standard area. The problems were found in the irrigation canal, which hampered the performance of irrigation downstream, where water cannot flow to rice fields. The wet cross-section of the channel is covered by sediment. Even at several locations, the sediment height has the same elevation as the surrounding surface. The purpose of this study is to obtain value in the form of an assessment index on the primary and secondary irrigation systems, which will be classified into their respective components. Furthermore, rehabilitation priority is determined using the decision-making method with the Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP). The assessment of irrigation performance index scored 62.94% consisting of physical infrastructure 29.28%; crop productivity 7.24%; supporting facilities 4.95%; personnel organization 10.75%; documentation 3.40%; and water user associations 7.33%. Determining the rehabilitation priority using the AHP method and ANP method showed the same results, i.e. physical infrastructure in rank 1, personnel organization in rank 2, crop productivity in rank 3, water user associations in rank 4, supporting facilities in rank 5, and documentation in rank 6. Determination of the selected rehabilitation in the physical infrastructure aspect is the sub-aspect of irrigation channels. Irrigation channels get the highest score with the worst damage conditions from all sub-aspects.